Empowerment-based ToT HIV intervention among Indonesian construction workers: a quasi-experimental study - Anisful Lailil Munawaroh; Fatma Lestari; Baiduri Widanarko (International Journal of Public Health Science (IJPHS), 2026)
Preventing HIV/AIDS in high-risk workplaces remains a public health priority, particularly in the construction sector. However, empirical evidence on structured, sustainable, and empowerment-based Training-of-Trainers (ToT) interventions for HIV prevention in Indonesian construction workplaces remains limited. This study evaluated a ToT-based intervention designed to build internal peer-facilitator capacity among construction workers and to strengthen workplace HIV prevention through a feasible, scalable, and participatory model. MA quasi-experimental single-group pre-test-post-test study was conducted among 30 construction workers attending a two-day facilitator training. HIV/AIDS knowledge was assessed before and immediately after training using a structured questionnaire. Paired-sample t-tests, Wilcoxon signed-rank test, Cohen’s dz, and thematic content analysis were applied. Results: Mean knowledge scores increased significantly from 60.00 (SD = 12.66) to 91.33 (SD = 7.65), with a mean difference of 31.33 (95% CI: 26.76-35.90; p < 0.001). These findings suggest that peer-facilitator training may be a promising workplace health promotion strategy to strengthen HIV prevention capacity in construction settings, although further controlled studies are needed. Qualitative findings highlighted increased confidence, perceived relevance, and stronger peer networking. The ToT-based intervention was associated with substantial short-term gains in HIV/AIDS knowledge among construction workers and may help strengthen internal workplace prevention capacity. Further controlled studies with longer follow-up are needed to confirm its effectiveness and sustainability.